Removal study of the hormone17 alpha‐ethynylestradiol and methylene blue dye from water using TiO2, Mn2O3 and TiO2/Mn2O3 thin flms - Paskocimas, Carlos Alberto (2021)
The disposal of pollutants in the surface, underground, and public water supply is an important problem, which is why it is necessary to study more efcient photocatalysts in the treatment of wastewater. In this context, thin flms of TiO2, Mn2O3 and TiO2/Mn2O3 were prepared by the hydrolysis of precursors in the presence of citric acid and ethylene glycol, to evaluate the photocatalytic performance in the degradation of methylene blue dye and the hormone 17a-ethinylestradiol (EE2), the measurements were repeated 10 times in a period of 300 min. Thin flms were deposited by spin-coating on Si (100) substrates and calcined at 500 °C and 600 °C for 2 h. Nanocomposites were characterized by X-ray difraction, atomic force microscopy, scanning electron microscopy, UV–visible spectroscopy, photocatalytic activity, and photoluminescence. X-ray difraction results revealed that no other phase was formed besides anatase and bixbite, indicating that there was no chemical interaction between the TiO2 and Mn2O3 layers. The results show the degradation values of methylene blue in approximately 57% and for the 17a-ethinylestradiol a degradation around 82%, showing that the studied photocatalysts are promising, mainly for the degradation of 17a-ethinylestradiol